Implementation of Multicultural Education Values in Senior High School - Rohmah, Hidayatur; Rena, Syahidah; Pahrurraji, Pahrurraji; Syarif, Fajar (At-tadzkir: Islamic Education Journal, 2023)
This research aims to describe and analyze the implementation of multicultural education values at Kharisma Bangsa Global Education High School in South Tangerang City and know the obstacles and challenges of implementing multicultural bathing there.  This research uses a qualitative approach with this type of case study research. Data sources are obtained from primary data sources (Principals, PAI Teachers, Academic Staff, and Kharisma Bangsa Learners) and secondary data sources from several books and others that support primary data. Data collection techniques are used through observation, interviews, and documentation. Then from some of the data that has been obtained the author performs data analysis techniques.  The results of this study show that 1). The implementation of multicultural education values at Kharisma Bangsa Global Education High School in South Tangerang City is the value of democracy, humanism, and tolerance, and the learning of multicultural Agama Islam (PAI) Education. These values are implemented through a whole school approach, dan 2). Obstacles and challenges in the implementation of multicultural educational values at Kharisma Bangsa High School are the adaptation of early learners into school, digital multicultural literacy, and awareness of understanding of multicultural education.